2020
DOI: 10.1002/ece3.6958
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary origins of taro (Colocasia esculenta) in Southeast Asia

Abstract: Before the Columbian exchange of crops between the Americas and the Old World, Colocasia esculenta (L.) Schott (taro, Araceae) was the world's most widespread food crop, grown in tropical to temperate

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 66 publications
(87 reference statements)
3
38
0
Order By: Relevance
“…No one single locus is good enough for evolutionary comparisons at all time scales; slow evolving regions should be preferred for deep divergences, while mutational hotspots for the closely related taxa and recently diverged species ( Ahmed et al, 2013 ; Ahmed, 2015 ; Li et al, 2020 ). A recent report of Ahmed et al (2020) on family Araceae showed the practical implication of the use of repeats in identification of suitable polymorphic loci for the study of phylogeography and population genetics. Their developed markers from the identified loci providing new insight about the origin of Colocasia esculenta in southeast Asia instead of Papua New Guinea ( Ahmed et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…No one single locus is good enough for evolutionary comparisons at all time scales; slow evolving regions should be preferred for deep divergences, while mutational hotspots for the closely related taxa and recently diverged species ( Ahmed et al, 2013 ; Ahmed, 2015 ; Li et al, 2020 ). A recent report of Ahmed et al (2020) on family Araceae showed the practical implication of the use of repeats in identification of suitable polymorphic loci for the study of phylogeography and population genetics. Their developed markers from the identified loci providing new insight about the origin of Colocasia esculenta in southeast Asia instead of Papua New Guinea ( Ahmed et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent report of Ahmed et al (2020) on family Araceae showed the practical implication of the use of repeats in identification of suitable polymorphic loci for the study of phylogeography and population genetics. Their developed markers from the identified loci providing new insight about the origin of Colocasia esculenta in southeast Asia instead of Papua New Guinea ( Ahmed et al, 2020 ). Our current results support strong associations between repeats and substitutions and repeats and InDels in Araceae, which can be helpful for identifying species-specific suitable loci for the study of phylogeography, domestication, and population genetics of other species of Araceae.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is mainly grown for its corm starch, which can be baked, fried, boiled, or made into fresh or fermented paste, flour, drink, crisps or chips. Additionally, its leaves are eaten in sauces, soups or stews due to the high content of vitamins, minerals, secondary metabolites and fiber [8,[14][15][16][17].…”
Section: The Energy and Nutritional Values Of Taromentioning
confidence: 99%
“…This is prokaryotic by the origin and shows uniparental inheritance paternal in some gymnosperm and maternal in most angiosperms [6][7][8]. The uniparental inheritance and differential mutation rate of different regions of the chloroplast genome makes it suitable for studies ranged from population genetics to phylogenetics [9,10]. Many mutational events occurred with chloroplast genomes, including InDels (insertions-deletions), substitutions, inversions, copy number variations, etc [11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%